2000
DOI: 10.1086/315823
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Infection in a Subset of HIV‐1–Positive Chimpanzees

Abstract: Chimpanzees are susceptible to infection with human immunodeficiency virus (HIV)-1; however, infected animals usually maintain normal numbers of CD4(+) T lymphocytes and do not develop immunodeficiency. We have examined 10 chronically infected HIV-1-positive chimpanzees for evidence of progressive infection. In addition to 1 animal that developed AIDS, 3 chimpanzees exhibit evidence of progressive HIV infection. All progressors have low CD4(+) T cell counts (<200 cells/microL), severe CD4:CD8 inversion, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 104 publications
4
42
0
Order By: Relevance
“…Lymph nodes from both animals prior to HIV-1 NC inoculation showed normal numbers of lymphocytes and little to no secondary follicle formation, similar to other age-matched HIV-negative and HIV-infected nonprogressor chimpanzees (30). The number and distribution of productively infected cells was determined in sections of lymph node by in situ hybridization for viral RNA, using a riboprobe that spans the entire HIV-1 genome, as described elsewhere (29,30).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Lymph nodes from both animals prior to HIV-1 NC inoculation showed normal numbers of lymphocytes and little to no secondary follicle formation, similar to other age-matched HIV-negative and HIV-infected nonprogressor chimpanzees (30). The number and distribution of productively infected cells was determined in sections of lymph node by in situ hybridization for viral RNA, using a riboprobe that spans the entire HIV-1 genome, as described elsewhere (29,30).…”
mentioning
confidence: 64%
“…The development of AIDS in C499 confirmed that pathogenic HIV infection can occur in experimentally infected chimpanzees (29). In addition, we recently described progressive HIV infection in other chimpanzees within the Yerkes cohort (30). Transfusion of blood from C499 to an uninfected chimpanzee, C455, resulted in a dramatic decline in CD4 ϩ T cells in the latter animal, which suggested the presence of a novel, chimpanzee-pathogenic HIV-1 isolate.…”
mentioning
confidence: 97%
“…Fifteen of these had been experimentally infected with HIV-1 more than a decade earlier as part of AIDS research studies (Table 1). Although five had significantly reduced CD4 counts (less than 200/mm 3 ; normal range 1,000 to 2,500/mm 3 ), none exhibited signs of clinical illness (35,36,39). Fecal and urine samples were also obtained from four SIVcpz-infected chimpanzees.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the case of HIV/SIV infection, a robust inflammatory response, necessary to recruit immune effector cells to the site of virus replication, may be detrimental to the host. In HIV type 1-infected patients, HIV-infected chimpanzees, and SIV-infected rhesus macaques, disease progression is associated with increased T-cell activation (9,18,23,26,28,34,39,41,42), while in African green monkeys and sooty mangabeys, the natural hosts of SIV, the virus replicates at high levels without causing disease and excessive immune activation (11,16,24,35,41). Thus, knowledge and understanding of the local cytokine milieu induced early after vaginal transmission may provide significant insight into new therapeutic interventions for virus transmission.…”
mentioning
confidence: 99%